MANAGEMENT IN PRESCHOOL EDUCATION ORGANIZATION. (Journal of Universal Science Research, 2023)
It is known that education is the process of conveying information of certain social importance to the younger generation. In a preschool educational institution, it is carried out in the classroom, on walks, in games, in communication with parents, etc. One of the most ancient types of human activity - child education has undergone significant changes during its centuries-old history of development, from a daily process to a complex of scientifically based systematic interaction based on the results of creative and creative activity. It is necessary to learn to manage the pedagogical process in a preschool educational institution under the conditions of introducing pedagogical technologies in the process. These processes were also studied in the article.